Variation rolls the dice a worldwide collage in honour of Salikoko S. Mufwene - Aboh, Enoch Oladé; Vigouroux, Cécile B.; Mufwene, Salikoko S. (Contact language library ;, 2021)
"Variation Rolls the Dice: A worldwide collage in honour of Salikoko Mufwene aims to celebrate Mufwene's ground-breaking contribution to linguistics in the past four decades. The title also encapsulates his approach to language as both systemic and socio-cultural practices, and the role of variation in determining particular evolutionary trajectories in specific linguistic ecologies. The book therefore focuses on variation within and across languages, within and across speakers, and how this fundamental aspect of human behavior can affect language structure in time and space. Mufwene has been instrumental in putting creole languages on the map of General Linguistics and connecting their analysis to issues of language acquisition, multilingualism, language contact, language evolution, and language typology. Thanks to the diversity of topics and the wide-ranging theoretical persuasions of the contributors, this volume aims at a large readership including both scholars and advanced students interested in cutting-edge research in the aforementioned domains"--